A Model of Housing in the Presence of Adjustment Costs: A Structural Interpretation of Habit Persistence - Flavin, Marjorie; Nakagawa, Shinobu (The American economic review, 2008)
The paper provides a model of household consumption and portfolio allocation which incorporates housing as both a consumption good and a component of wealth. Household utility depends, possibly nonseparably, on two goods: nondurable consumption, which is costlessly adjustable, and housing, which is subject to a nonconvex adjustment cost. Households face housing price risk in the sense that the relative price of housing varies over time, and can invest in a wide variety of financial assets in addition to housing. This single, reasonably tractable, model generates testable implications for portfolio allocation, risk aversion, asset pricing, and the dynamics of nondurable consumption. (JEL D14, G11, R21)